PENGEMBANGAN MEDIA PEMBELAJARAN E-LEARNING BERBASIS WEB UNTUK MATA KULIAH PENDAHULUAN FISIKA INTI - iful amri; Syuhendri Syuhendri; Ketang Wiyono (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2015)
It has done other research development to produce instructional media web-based e-Learning courses Introduction to Physics Core. Development of research models used is the 4D model, which includes the step of defining, designing, development, and deployment. At defining stage consists of front-end analysis, analysis of student, tasks and concepts, as well as learning objectives. At the design stage consisted of drafting to design activities carried out in the form of e-Learning web. Then, the stage of development consists of e-Learning web validation, and test limited to the students to see the practicality. While the deployment phase is not implemented. The instruments used are (1) sheet validation experts (2) student questionnaire responses, and (3) observation sheet. Based on the assessment of experts, the average total validity (RTV) e-Learning web-developed is the web RTV ≤ 4 ≤ 5, namely sebesar4,55. RTV values ​​are included in the category of very valid. Based on the questionnaire responses of students who tested on 31 students, web e-Learning practical expressed with a percentage of 75.44% and the percentage of enforceability limited trial based on observation of student activity 84.03%. It was concluded that the e-Learning web courses Introductory Physics Core has been developed to meet the criteria of validity and practicality as well as meet the rules of development in accordance with the purpose of learning and applicable curriculum